PENGEMBANGAN E-MODUL GELOMBANG DALAM MEMFASILITASI KESIAPSIAGAAN BENCANA GEMPA BUMI SISWA SMA - Hidayatullah, Subhan; Haryadi, Rudi; Guntara, Yudi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
Earthquake is one of the natural disasters that can cause serious damage to buildings and nature. Therefore, integration of learning materials in schools is needed so that students know and understand earthquake disaster preparedness. In addition, mechanical waves are one of the physics learning materials that are quite difficult due to the lack of teaching materials that can discuss contextually. This is in line with earthquake disasters which are also caused by waves. Therefore, an e-module wave was created that facilitates student disaster preparedness that can be opened anytime and anywhere. This research and development aims to obtain data on the feasibility and validity of teaching materials and to determine the response of students to the wave e-module teaching material in facilitating high school students' earthquake disaster preparedness. The data from the validation of the instrument obtained were 93.33% for the feasibility of the material and 91.74% for the feasibility of the media. While the limited trial conducted on students obtained an average value of 92.5%.